Factors Affecting Work Outcomes on the Educators’ Continuous Usage Behaviour of Learning Management System (LMS): A Proposed Conceptual Framework - Mohd Fisol, Nabilah (GATR Enterprise, 2015)
Objective – This paper develops a theoretical framework that consists of the factors affecting the work outcomes among educator continuous usage behaviour of Learning Management System (LMS). Methodology/Technique – The conceptual framework is based on the previous literature review and the underpinning theories which are an integral of Technology Acceptance Model (TAM) and IS Continuance Model. Perceived usefulness, perceived ease of use and confirmation are identified as independent variables; satisfaction and IS continuance intention will be employed as mediating variable; and work outcomes as a dependent variable. Findings – In this study, 13 hypotheses have been proposed based on the conceptual framework outlined. The proposed framework would help the organizations to plan for the potential improvement of the systems and teaching strategies in the context of the LMS, in order to meet the educational goals and to get better learning outcomes. Novelty – Currently, there are very limited empirical researches that have been conducted on educator’s outcomes on the post-adoption stage of LMS. Type of Paper: Conceptual